PENGARUH KOMPETENSI GURU TERHADAP HASIL BELAJAR DENGAN VARIABEL KONTROL PENGETAHUAN AWAL : Survey pada Peserta didik Kelas XI IPS SMA Negeri se-Kota Bandung - Purwanti, Suci Tresna (2017)
The main problem in this research is the decrease of students' learning result of Senior High School in Bandung as seen from the average score of National Exam on economic subjects. This study aims to investigate the influence of teacher competence, including pedagogic competence, personality competence, social competence and professional competence on students' learning outcomes on economic subjects as seen from the prior knowledge of the students. The research method used in this research is explanatory survey. The population in this study was the students of class XI IPS in Senior High School in Bandung as many as 781 students. By using sample random sampling technique and proportional random sampling, there were 265 students as the sample. Data analysis technique used in this research is multiple linear regressions. The results of the study showed that: (1) student learning outcomes were mostly in the category above the minimum masterycriteria (KKM), teacher competence assessed based on the students' perception, both pedagogic competence was in high category, personality competence was in moderate category, social competence was in the moderate category, and professional competence was in the moderate category, on the other hand, the prior knowledge of the students is mostly in the category above the minimum masterycriteria (KKM); (2) teacher pedagogic competence have a positive and significant effect on students' learning result, the teacher's personality competence has no effect on the students' learning result, teacher's social competence has positive and significant effect on students' learning result, teacher's professional competence has positive and significant effect on students' learning result; (3) teacher competence as seen from the prior knowledge of the students have a positive and significant effect on student learning outcomes.---- Permasalahan dalam penelitian ini adalah adanya penurunan hasil belajar siswa SMA Negeri se-Kota Bandung dilihat dari nilai rata-rata ujian nasional pada mata pelajaran ekonomi. Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi guru, baik kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial dan kompetensi profesional terhadap hasil belajar siswa pada mata pelajaran ekonomi dilihat dari pengetahuan awal siswa. Metode penelitian yang digunakan yaitu survei eksplanatori. Populasi dalam penelitian adalah siswa kelas XI IPS SMA Negeri se-Kota Bandung sebanyak 781 siswa. Dengan menggunakan teknik sampel random sampling dan proportional random sampling diperoleh sampel sebanyak 265 siswa. Teknik analisis data yang digunakan yaitu regresi linier berganda. Hasil penelitian menunjukan bahwa: (1) hasil belajar siswa sebagian besar berada pada kategori diatas nilai kriteria ketuntasan minimum (KKM), kompetensi guru yang dinilai menurut persepsi siswa, baik kompetensi pedagogik berada pada kategori tinggi, kompetensi kepribadian berada pada kategori sedang, kompetensi sosial berada pada kategori sedang, dan kompetensi profesional berada pada kategori sedang, sedangkan pengetahuan awal siswa sebagian besar berada pada kategori diatas nilai kriteria ketuntasan minimum (KKM); (2) kompetensi pedagogik guru berpengaruh positif dan signifikan terhadap hasil belajar siswa, kompetensi kepribadian guru tidak berpengaruh terhadap hasil belajar siswa, kompetensi sosial guru berpengaruh positif dan signifikan terhadap hasil belajar siswa, kompetensi profesional guru berpengaruh positif dan signifikan terhadap hasil belajar siswa; (3) kompetensi guru jika dilihat dari pengetahuan awal siswa berpengaruh positif dan signifikan terhadap hasil belajar siswa.